Islam and media in contemporary Nigeria - Ashimi, Tijani Ahmad (2014)
Islam is one of the major religions in the contemporary Nigeria; it dominates in the north and holds strong numbers in the south western part of the country. The print media in general and some Nigerian newspapers in particular are known to have been fueling religious conflict and disharmony in Nigeria. The Nigerian newspapers depict Islamic shari‘ah in a horribly negative manner. This article tries to highlight how some Nigerian newspapers purposely try to sabotage national harmony, on the one hand, and extend suggestions to Nigerian print media that can be utilized to strengthen and enhance religious tolerance, peace, harmony, and unity in Nigerian Society, on the other.